Dampak Siklon Tropis Savannah Terhadap Karakteristik Hidrogeokimia Aliran pada Mata Air Guntur, Kawasan Karst Gunungsewu - Fajri Ramadhan; Indra Agus Riyanto; Ahmad Cahyadi; Muhammad Naufal; M Widyastuti; Tjahyo Nugroho Adji (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2021)
Tropical Cyclones often occur in Indonesia and have disastrous impacts. Until now, no research has focused on time series data related to groundwater discharge and chemistry due to tropical cyclones. Therefore, this study aims to analyze and compare the characteristics of the hourly time series, both discharge and chemistry of the Guntur karst springs. Guntur Spring was affected by the tropical cyclone of Savannah on March 17, 2019. The method used in this study consisted of two parts, namely the analysis of the discharge and chemistry of Guntur Spring. Discharge analysis was performed by correlation test with rain intensity. Chemical analysis was carried out using the Minister of Health Regulation No. 90 of 2002 and expert standards. Other chemical analyzes were performed using a triangular piper, rectangular piper, and stiff diagram of the parameters Na+, K+, Ca2+, Mg2+, SO42-, Cl-, and HCO3-. The results of the relationship between discharge and rain intensity are directly proportional and increase significantly during a cyclone. The results of analysis of the Guntur Springs during Tropical Cyclone Savannah, all parameters are in accordance with the quality standard. In addition, there was a reduction in ion content due to the dilution process of Ca2+, Mg2+, Cl-, HCO3-., DHL, and pH ions compared to non-cyclone, Beton Resurgence, and Gremeng Resurgence ions. The chemical results when the cyclone is different compared to non-cyclone, Gremeng Resurgence and Beton Resurgence with a characteristic decrease in ionic content.